2020
DOI: 10.3390/nano10010106
|View full text |Cite
|
Sign up to set email alerts
|

Nanotip Contacts for Electric Transport and Field Emission Characterization of Ultrathin MoS2 Flakes

Abstract: We report a facile approach based on piezoelectric-driven nanotips inside a scanning electron microscope to contact and electrically characterize ultrathin MoS2 (molybdenum disulfide) flakes on a SiO2/Si (silicon dioxide/silicon) substrate. We apply such a method to analyze the electric transport and field emission properties of chemical vapor deposition-synthesized monolayer MoS2, used as the channel of back-gate field effect transistors. We study the effects of the gate-voltage range and sweeping time on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

8
2

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 78 publications
1
21
0
Order By: Relevance
“…The isolation of graphene [1][2][3] in 2004 and, later on, of h-BN [4], phosphorene [5], S Mo 2 [6][7][8][9][10][11][12][13][14], WSe 2 [15][16][17], e PdS 2 [18,19], PtSe 2 [20,21] etc, has strongly attracted the interest of the material science community to the world of two-dimensional (2D) materials.…”
Section: Introductionmentioning
confidence: 99%
“…The isolation of graphene [1][2][3] in 2004 and, later on, of h-BN [4], phosphorene [5], S Mo 2 [6][7][8][9][10][11][12][13][14], WSe 2 [15][16][17], e PdS 2 [18,19], PtSe 2 [20,21] etc, has strongly attracted the interest of the material science community to the world of two-dimensional (2D) materials.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 Several transition metal dichalcogenides (TMDs) have promptly emerged as possible substitutes or complements to graphene 4 and have already been investigated and proposed for several applications. 5 13 More recently, the search for new types of 2D materials has led to the investigation of binary compounds of IV and V groups. Indeed, theoretical calculations have indicated that MX compounds, with M = Si, Ge, Sn, or Pb and X = P, As, Sb, or Bi, might have crystalline layered structures with orthorhombic ( Cmc 2 1 for SiP and Pbam for SiP 2 and GeAs 2 ) or monoclinic ( C 2/ m for GeP, GeAs, and SiAs) symmetries.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4–9 ] However, the difficulty in selecting the desired CNT properties during the production process, commonly leading to a mixture of metallic and semiconducting CNTs in the final product, makes their use in technological applications an open challenge. In recent years, inorganic layered materials, such as MoS 2, [ 10–13 ] PdSe 2, [ 14–16 ] WSe, [ 17,18 ] WS 2 , [ 19 ] and GeAs [ 20 ] have been widely studied for their unique electrical and optical properties. In particular, WS 2 has a layered structure where monolayers, constituted by a plane of W atoms sandwiched between two planes of S atoms, are piled on top of each other and bonded by weak van der Waals forces.…”
Section: Introductionmentioning
confidence: 99%